Determinants of Success and Early Complications in Common Femoral Artery Endarterectomy: A Retrospective Study - Marcel Libertus Johannes Quax; Daniël Eefting; Herman Joseph Smeets (Surgeries, 2021)
Introduction: Common femoral artery endarterectomy (CFE) is considered a relatively simple, successful and safe procedure in the literature, but major complications can occur. This retrospective study was performed in order to define characteristics contributing to success or failure after common femoral artery endarterectomy, either performed as a single or hybrid procedure. Methods: A total of 298 patients who underwent CFE in our hospital between 1 January 2011 and 1 January 2017 were included. After exclusion, 227 patients were analyzed. Patient characteristics and outcomes were derived from the patient records. Follow-up was 30 days postoperatively. Outcomes were analyzed by the chi-square test and regression analysis. Clinical success was defined as a combination of technical success, improvement in the ankle-brachial index, increased walking distance and “no complications.” Results: The procedure was clinically successful in 74.4% of the patients, and in 25.6%, a complication occurred. The Rutherford class improved in 65.1% of the patients with 1.6 (SD 1.3) class points. The ankle-brachial index improved in 44.8% of the cases, with an average of 116.6%. The most contributing factors for complications such as death, unplanned amputation, surgical site infection, thrombosis and longer hospital admission were emergency operation and a higher ASA classification. Significantly more complications also occurred in patients with renal failure, congestive heart disease, a high Rutherford classification and previous groin incision. A higher Rutherford class was the only factor correlating with an increase in the ankle-brachial index. When single CFE (48.9% of cases) and hybrid procedures (51.1%) were compared, no significant difference in success or failure was found. Conclusion: Limb ischemia requiring emergency operation and preoperative comorbidity were identified as the most important factors predictive for complications following femoral artery endarterectomy. Combining femoral endarterectomy with an endovascular intervention does not seem to increase the risk of a postoperative complication.